ICoLLT 2018 has wrapped up - Hanisah, Kasbon (2018)
Held on 25-26 June 2018 in Pekan, Pahang, the 2nd International Conference on Language Learning and Teaching (ICoLLT) hosted by the Centre for Modern Languages and Human Sciences (CMLHS), Universiti Malaysia Pahang (UMP) was a very successful event. Over 100 delegates attended and participated in the two-day conference, which brought together school teachers and academics within the Malaysian universities and some other Asian countries to touch upon the broad theme of this year’s conference, “Innovation and Global Challenges in Language Education”. The conference was officially opened by Associate Professor Dr Muhamad Nubli Abdul Wahab, the Dean of the CMLHS.